2020
DOI: 10.3390/s20143879
|View full text |Cite
|
Sign up to set email alerts
|

Sign Language Recognition Using Wearable Electronics: Implementing k-Nearest Neighbors with Dynamic Time Warping and Convolutional Neural Network Algorithms

Abstract: We propose a sign language recognition system based on wearable electronics and two different classification algorithms. The wearable electronics were made of a sensory glove and inertial measurement units to gather fingers, wrist, and arm/forearm movements. The classifiers were k-Nearest Neighbors with Dynamic Time Warping (that is a non-parametric method) and Convolutional Neural Networks (that is a parametric method). Ten sign-words were considered from the Italian Sign Language: cose, grazie, maestra, toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Other recent studies presented frameworks and techniques that have been developed to solve the SLR problem, focusing on signal processing for sensors with different natures. For example, a leap motion sensor was used with a hidden Markov layer for pattern recognition of 24 gestures of ASL [41] and instrumented gloves with flex [42] and/or inertial sensors [43] with machine learning techniques reached accuracies ranging from 86% to 98%. A combination of images and deep learning techniques demonstrated high performance for this task, such as for Persian Sign Language [44] and CSL [45].…”
Section: Related Workmentioning
confidence: 99%
“…Other recent studies presented frameworks and techniques that have been developed to solve the SLR problem, focusing on signal processing for sensors with different natures. For example, a leap motion sensor was used with a hidden Markov layer for pattern recognition of 24 gestures of ASL [41] and instrumented gloves with flex [42] and/or inertial sensors [43] with machine learning techniques reached accuracies ranging from 86% to 98%. A combination of images and deep learning techniques demonstrated high performance for this task, such as for Persian Sign Language [44] and CSL [45].…”
Section: Related Workmentioning
confidence: 99%
“…To the best of our knowledge, studies reported in [27,32] and [33] adopt approaches comparable with the technique here presented. In [27], the commercial sensory glove Cyberglove TM is exploited to acquire data about hand configuration, while the Flock of Birds ® motion tracker provides data about hand position and orientation.…”
Section: State Of the Artmentioning
confidence: 99%
“…They reached 91% recognition accuracy for a dataset of 95 categories of Australian sign language. In [33], a wearable system with 10 flex sensors in a glove and 3 IMUs has been used for data acquisition. In that paper, a k-Nearest Neighbors with Dynamic Time Warping and Convolutional Neural Networks has been applied to classify among 10 signed-words from the Italian Sign Language.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other end, wearable technology has been proving to produce convincing and useful results in evaluating motor impairments of subjects suffering from (among others) Parkinson disease [10][11][12], attention deficit hyperactivity disorder/developmental coordination disorder (ADHD/DCD) [13], neuro-degenerative diseases [14], or spinal cord injury [15], when measured in a clinical environment, and in evaluating motor (dis)abilities of subjects when doing daily chores in home environment too [16][17][18]. The effective sensitivity of instruments as accelerometers, gyroscopes [19,20], and electromyography (EMG) [21], supports and extends the naked-eye analysis of the medical doctors [22] for the balance and gait analysis: Chapron et al adopted wearable IMUs on patients during physical rehabilitation programs within domestic environments [23]. Storm et al found that IMUs applied to the six-minute walk trial can provide clinically meaningful information [24].…”
Section: Introductionmentioning
confidence: 99%